Evaluation of the effects of an artificial intelligence system on endoscopy quality and preliminary testing of its performance in detecting early gastric cancer: a randomized controlled trial - Wu, Lianlian; He, Xinqi; Liu, Mei; Xie, Huaping; An, Ping; Zhang, Jun; Zhang, Heng; Ai, Yaowei; Tong, Qiaoyun; Guo, Mingwen; Huang, Manling; Ge, Cunjin; Yang, Zhi; Yuan, Jingping; Liu, Jun; Zhou, Wei; Jiang, Xiaoda; Huang, Xu; Mu, Ganggang; Wan, Xinyue; Li, Yanxia; Wang, Hongguang; Wang, Yonggui; Zhang, Hongfeng; Chen, Di; Gong, Dexin; Wang, Jing; Huang, Li; Li, Jia; Yao, Liwen; Zhu, Yijie; Yu, Honggang (Endoscopy, 2021)
Background Esophagogastroduodenoscopy (EGD) is a prerequisite for detecting upper gastrointestinal lesions especially early gastric cancer (EGC). An artificial intelligence system has been shown to monitor blind spots during EGD. In this study, we updated the system (ENDOANGEL), verified its effectiveness in improving endoscopy quality, and pretested its performance in detecting EGC in a multicenter randomized controlled trial.Methods ENDOANGEL was developed using deep convolutional neural networks and deep reinforcement learning. Patients undergoing EGD in five hospitals were randomly assigned to the ENDOANGEL-assisted group or to a control group without use of ENDOANGEL. The primary outcome was the number of blind spots. Secondary outcomes included performance of ENDOANGEL in predicting EGC in a clinical setting.Results 1050 patients were randomized, and 498 and 504 patients in the ENDOANGEL and control groups, respectively, were analyzed. Compared with the control group, the ENDOANGEL group had fewer blind spots (mean 5.38 [standard deviation (SD) 4.32] vs. 9.82 [SD 4.98]; P < 0.001) and longer inspection time (5.40 [SD 3.82] vs. 4.38 [SD 3.91] minutes; P < 0.001). In the ENDOANGEL group, 196 gastric lesions with pathological results were identified. ENDOANGEL correctly predicted all three EGCs (one mucosal carcinoma and two high grade neoplasias) and two advanced gastric cancers, with a per-lesion accuracy of 84.7 %, sensitivity of 100 %, and specificity of 84.3 % for detecting gastric cancer.Conclusions In this multicenter study, ENDOANGEL was an effective and robust system to improve the quality of EGD and has the potential to detect EGC in real time.